SOCIAL PHENOMENON IN POETRY MONEY MESSAGE AND SHAVE BEFORE SLEEP BY JOKO PINURBO - Irsyad Zulfahmi (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2014)
The objective of the reserch is to identify the picture of social conditions contained in two poems by Joko Pinurbo, namely the Money Message and Shave Before Sleeping.Based on the  results  of research conducted, it can be concluded; in form, the poem Messages Money consists of four temple and fifteen rows, depicting how someone who tried to improve the conditions  of life by "wander", which then have an impact not only on the material but also on the moral side.Meanwhile, in a poem titled Shave Before Sleeping in shape, consisting of 28 arrays of 2 stanza. The poet uses the metaphor of the body as a natural phenomenon, this is where the poet actually want to describe the rate of development  of  advanced   industrial  however  less  attention  to  the  preservation  of  the natural environment.